Ithbat al-mawarith fi zill al-thawabat wa-al-mutaghayyirat : dirasah tahliliyah = Fixed and flexibilities of the Islamic law of succession : an analysis / Raouane Azziz Bachir - Bachir, Raouane Azziz (2011)
The syariah law is clear and absolute. However, the worldly life occurrences of humans are infinite, creating endless issues. Therefore ijtihad is required in solving these infinite issues, The Islamic syariah law, was very clearly elucidated in the early years it was first introduced to the ummah. However, as time passes, ijtihad was seen accepted without questions, and signs of disillusion started to appear. This in return, led to the weakening within the ummah itself, thus making us more sluggish in our development. It is crucial that the Islamic scholars who are well equipped with the knowledge within this area to work together in contributing to ijtihad in the Islamic syariah law. The writer wishes to enlighten the ummah on matters regarding the inheritance by incorporating the knowledge of modern science within the Islamic syariah law itself. The writer has traced back the inductive approach which is in line with the nature of this research itself. He has cross-referenced multiple sources and articles, and then applied this approach to jurisprudence in the subject of inheritance. The writer divides this discussion into two sections: Islamic law of inheritance; which is definite and secondly; knowledge that change such as hermaphrodite, pregnancy and missing person. The later subject is discuss in detail with the presence of the scientific evidence; a paradigm shift in the knowledge of Islamic law in inheritance. The contribution of science knowledge (medicine, forensic science, telecommunications) in understanding many of the provisions we thought in the past were conclusive, when confronted and recognized then for the first time. However the veiled knowledge can now be revealed by the scientists, the time has come to make a paradigm shift. The researcher sought to benefit from modern science and applies them to some of the provisions of inheritance, for example the knowledge of hermoprodite, the viability length of pregnancy, and DNA evidence. These results are very important because they are able to provide new things in Islamic law of inheritance; consolidating the concepts of jurisprudence, and to know that science is the largest server of the religion and both science and religion is inseparable. Furthermore the development of science has increased firmness of Islam and its clarification.